Creare nuove enclosures. La ripetizione violenta dell’accumulazione primitiva attraverso degradazione delle donne, lockdown, finanza predatoria, guerra, saccheggio dei beni comuni - Magnani, Lorenzo; Marchini, Anna Maria (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2025)
Starting from the analysis of the chapter of Marx contained in the first volume of Capital, this article describes the Marxian emphasis on the extremely violent aspects – a list of the main cases is also provided – of the so-called "enclosures" as fundamental procedures that favored “primitive accumulation” (or original accumulation), that is, the first social and economic step that led to capitalism. The implementation of the "enclosures" that characterized the process of primitive accumulation is illustrated in detail, violently expropriating the peasants, razing their cottages and their homes to the ground. At the same time, we will describe what we call the "moral bubble", created by the – morally edifying – narratives on the enclosures, dedicated only to the emphasis on positive economic and social results: the moral bubble acts as a powerful conceptual device capable of hiding the violence that accompanies the enclosures. The second part of the article underlines the fact that the mechanism of enclosures can be traced back not only to the violent expropriation of common lands where peasants previously thrived, but also to the processes of violence against women to substantially reduce them to machines for the production of new workers, in the framework of the new "wage patriarchy". The importance of the so-called "new enclosures" is further outlined after showing how the enclosures express the historical and general tendency of capitalist accumulation and not only of the primitive one. The analogous violent aspects of primitive accumulation, and therefore of primitive enclosures, are described as the protagonists of every phase of the recent capitalist globalization, marked by a continuous and unprecedented assault (as an intelligent social, political and economic mechanism to produce enclosures) on common goods, perpetrated by the World Bank, the International Monetary Fund, the lockdown for the coronavirus and, currently, also by the paradoxical economic effects of the interaction between the green era and the Ukraine war/global food and energy crisis. Finally, the last paragraph provides information on what we have called "terminal enclosure" linked to the aggression of the common good par excellence: water. Enclosures; Capitalism; Morality; Violence.